Toxicity and Antimicrobial Activity of Zerumbon from Zingiber zerumbet Rhizome - Hartiwi Diastuti; Ari Asnani; Eva Vaulina Yulistia Delsy; Restu Pamukasari; Sri Indriani (Universitas Jenderal Soedirman, 2022)
Zingiber zerumbet is a medicinal plant that has the potential as a source of bioactive compounds. Zerumbone is a major compound of the essential oil fraction of Z. zerumbet. Research on antimicrobial activity and toxicity of zerumbone is still very limited. In this study, the zerumbone was isolated from Z. zerumbet rhizome and then studied for its potential as an antimicrobial agent and toxicity properties. The isolation of the zerumbone compound was carried out through extraction, fractionation, and purification. The structure of zerumbone was determined by an NMR spectrophotometer (1D and 2D) and GCMS. The toxicity assay was carried out using the Brine Shrimp Lethality Test (BSLT) method, while the antimicrobial activity assay was carried out using the microdilution method against, Escherichia coli, Propionibacterium acnes, Staphylococcus aureus, Bacillus ceureus, Candida albicans, Malasezia furfur, and Aspergillus sp. The isolation of zerumbone from the n-hexane fraction of Z. zerumbet rhizome obtained a pure compound in the form of white crystals, with a melting point of 65.5 ºC. Toxicity assay of zerumbone was obtained LC50 values ​​of 21.29 µg/mL. The activity assays on the seven test microbes showed potential activities with a range of MIC values ​​of 15.62–250 µg/mL. Zerumbone has the highest activity against Aspergillus sp with the MIC value of 15.62 µg/mL.